2021
DOI: 10.1108/jedt-02-2021-0080
|View full text |Cite
|
Sign up to set email alerts
|

Waste utilization to enhance performance of road subbase fill

Abstract: Purpose The purpose of this study is to use waste materials in construction to create sustainable practices. This will contribute towards circular economy which has gained momentum in recent years throughout the world. Design/methodology/approach Waste materials cause enormous environmental problems that can have an adverse effect on the environment. Recycling of waste consists an important part of the circular economy. Therefore, researchers have been investigating the economic use of a variety of waste mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…This improvement can be explained by the cation exchange reaction between calcium ions of lime and the exchangeable ions of the soil surface, which produced a flocculated soil structure with an open soil fabric; consequently, the internal friction angle significantly improved and resulted in a higher CBR value. The same behavior was observed by other researchers [32][33][34][35] when studying the strength and microstructural behavior of lime stabilized subgrade soil in road construction. According to Figure 16, the combinations meeting the load-bearing criteria are soil+20% sand+20% natural pozzolana stabilized with 3% and 5% lime when the load-bearing index is greater than 25, so the stabilized soil can be used as a layer of foundation.…”
Section: California Bearing Ratio (Cbr)supporting
confidence: 87%
“…This improvement can be explained by the cation exchange reaction between calcium ions of lime and the exchangeable ions of the soil surface, which produced a flocculated soil structure with an open soil fabric; consequently, the internal friction angle significantly improved and resulted in a higher CBR value. The same behavior was observed by other researchers [32][33][34][35] when studying the strength and microstructural behavior of lime stabilized subgrade soil in road construction. According to Figure 16, the combinations meeting the load-bearing criteria are soil+20% sand+20% natural pozzolana stabilized with 3% and 5% lime when the load-bearing index is greater than 25, so the stabilized soil can be used as a layer of foundation.…”
Section: California Bearing Ratio (Cbr)supporting
confidence: 87%
“…Therefore, countries with frequent cycles of demolition of old structures and construction works are exploring ways to use RA produced from such activities. Recycling and reuse of C&D waste are important for sustainable development and maintaining an eco-friendly green environment (Bui et al , 2017; Onturk et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Pateriya et al [16] tried stabilising weak soil using marble waste blended with fly ash, cement, and nanomaterials, and the outcomes revealed that such a blended mix acts as a potential source for stabilising weak soil. ere has been a lot of research done on other waste items like granite waste, oxygen furnace slag, and fly ash [17,18]. Because of the presence of silica, glass wastes can be utilised in multiple ways in the construction industry: as fine aggregate in the form of glass powder [19,20], as glass fibres in fibre reinforced concrete [21], and even as a stabilising agent in weak soil [22,23].…”
Section: E Use Of Waste Materials Such As Soil Stabilizersmentioning
confidence: 99%